The Reputational Impact of Investor-State Disputes. Issue 5 (3rd September 2018) - Minhas, Shahryar; Remmer, Karen L.
ABSTRACT: To what extent do alleged violations of international commitments damage state reputation? This article explore this question with specific reference to investor-state disputes arising under the protection of international investment agreements. Its main contributions are threefold. First, building on the political institutions literature, the study places the theoretical importance of information about the rules of the game, and the actions of the participants at the center of analysis. Second, in contrast to prior empirical research, the study systematically analyzes the costs of state involvement in investment treaty arbitration by examining all known disputes. Third, the study addresses the impact of investment disputes on both foreign investment flows and state reputational rankings. We show that the consequences of investment disputes vary with the transparency of the investor-state dispute settlement process. The central implication of these findings for the broader body of literature on international institutions is that reputational mechanisms for effective treaty enforcement cannot be taken as given but instead need to be explored on the basis of a nuanced approach that addresses the pivotal issues of institutional design and information costs.